Monocytes and macrophages in heart valves: Uninvited guests or critical performers?. (March 2018) - Sridhar, Sraeyes; Pham, Duc H.; Gee, Terence W.; Hua, Joanna; Butcher, Jonathan T.
Abstract: Monocytes and macrophages are critical components of the myeloid niche of the innate immune system. In addition to traditional roles as phagocytes, this subsection of innate immunity has been implicated in its ability to regulate tissue homeostasis and inflammation across diverse physiological systems. Emergence of discriminatory features within the monocyte/macrophage niche within the last 5 years has helped to clarify specific function(s) of the subpopulations of these cells. It is becoming increasingly aware that these cells are likely implicated in valve development, disease, and tissue engineering outcomes. This review seeks to use current literature and opinions to show the diverse roles and potential contributions of this niche throughout valvulogenic processes, adult homeostatic function, valve disease mechanisms, and tissue engineering approaches. Graphical abstract: Monocyte and macrophage regulation of valvular activity from valvulogenesis, homeostasis, disease mechanisms, and tissue engineering approaches. Highlights: We highlight potential mechanisms of myeloid contributions to valve development. We highlight potential mechanisms of myeloid involvement in valve disease, and the gaps in knowledge that require further investigation. We highlight monocytes and macrophages as therapeutic targets towards tissue engineered heart valves.